Applications of atomic force microscopy-based imaging and force spectroscopy in assessing environmental interfacial processes. Issue 14 (18th July 2022) - Zhang, Yuyao; Zhu, Xiaoying; Chu, Chiheng; Xiao, Xin; Chen, Baoliang
Abstract: The interfacial physicochemical processes play  critical roles in the transport and fate of contaminants in natural environment, yet assessments of these processes are limited by the lack of proper in-situ tools. Recent advances in atomic force microscopy (AFM) techniques lead to new opportunities for in-situ probing these processes, which may provide in-situ information on adsorption kinetics, diffusion pathways, and deposition morphology. In this review, we provided a systematic summary of the progress and achievements in applications of AFM techniques for studying environmental interfacial processes, properties, and molecular interactions, with the primary target of clarifying the fundamental principles that correlate the uniqueness of AFM techniques with the specific and practical demands for environmental studies. Modifying the AFM tips with target compounds allows direct measurements of interfacial properties such as surface hydrophobicity, acid dissociation constant and isoelectric point. Moreover, the interfacial interactions between contaminants and environmental matrixes can be quantified at the molecular level utilizing single-molecule force spectroscopy and atomic-resolution AFM imaging. The environmental interfacial behaviors assessed by AFM-based techniques are essential for revealing the environmental dynamics and risks of contaminants. Finally, the future needs on AFM tips modification and application of AFM in assessing environmental interfacial processes are prospected. Graphical abstract: UF0001